Optimasi Produksi Roti Di Grace Bakery Dengan Menggunakan Integer Goal Programming - Lumanaw, Joshua Apriano; Mangobi, James Uriel Livingstone; Maukar, Marvel Grace (KUBIK, 2024)
Grace bakery is a home industry in making bread. The problem experienced by Grace Bakery is that Grace Bakery has not planned to optimize bread production, this has caused losses for Grace Bakery and sales have not been maximized. This research aims to formulate a mathematical model for optimizing bread production using integer goal programming and to obtain optimization results for bread production planning using integer goal programming with the help of the Lingo application. The method used to solve this integer goal programming problem is branch and bound. By using integer goal programming, the branch and bound method and with the help of the Lingo application, the research results show that Grace Bakery must produce 3993 chocolate breads, 1334 cheese breads and 4237 mocha breads every month so that Grace Bakery will earn a maximum income of Rp. 17.280.000. Revenue will reach optimal results if all the bread is sold out and there is no increase in raw materials. Grace bakery can also reduce production costs to Rp. 11.670.092,5 every month.